2020
DOI: 10.1038/s41598-020-61748-y
|View full text |Cite
|
Sign up to set email alerts
|

Futile complete recanalization: patients characteristics and its time course

Abstract: As the goal of mechanical thrombectomy is shifting toward mTICI-3 rather than mTICI-2b, we sought to clarify the limitation of the effect of mTICI-3. A post-hoc analysis of a registry of large-vessel occlusion stroke from 46 centers was conducted. Among 2,420 registered patients, 725 patients with anterior circulation occlusion who achieved successful reperfusion were analyzed. We compared outcomes between patients with mTICI-3 and mTICI-2b, and investigated how the effect of mTICI-3 changed according to basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
(47 reference statements)
0
15
1
Order By: Relevance
“…Although the technical expertise of the operator is important, the increased number of passages may be due to some uncontrollable factors such as increased clot fragmentation with distal embolization or accumulated endothelial damage (27). In addition, the impact of the groin to recanalization and the number of passages on futile recanalization supports the conclusion of previous studies that an angiographic recanalization does not necessarily lead to functional independence if it was achieved at the expense of longer procedural times (28).…”
Section: Figurementioning
confidence: 58%
“…Although the technical expertise of the operator is important, the increased number of passages may be due to some uncontrollable factors such as increased clot fragmentation with distal embolization or accumulated endothelial damage (27). In addition, the impact of the groin to recanalization and the number of passages on futile recanalization supports the conclusion of previous studies that an angiographic recanalization does not necessarily lead to functional independence if it was achieved at the expense of longer procedural times (28).…”
Section: Figurementioning
confidence: 58%
“…28,29 On the other hand, recent analyses from the RESCUE-Japan 2 Registry suggested that mTICI 3 versus mTICI 2b was associated with favorable outcomes only when puncture to reperfusion time was <80 min. 30 In this analysis, the association of EARI with higher rates of functional independence was relatively homogenous across subgroups (including different time intervals from symptom onset to IAF) with one exception. Although not significant on interaction analyses, there was a tendency of the association being attenuated in patients with moderate to severe ischemia as opposed to those without or only minor ischemic changes on admission.…”
Section: Discussionmentioning
confidence: 72%
“…In general, increasing the number of passes and increasing the treatment time to achieve successful reperfusion were shown to lead to worse functional outcome 1 6–12. This trend to worse functional outcome was also seen when excellent or complete reperfusion (eTICI 2C/3) was reached 6 13. However, in patients with complete reperfusion a decline in the odds of post-stroke functional independence was only seen if more than three passes were necessary to achieve this result, while in patients with a final eTICI score of 2B this decline had already occurred if more than two passes were necessary 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with complete reperfusion a decline in the odds of post-stroke functional independence was only seen if more than three passes were necessary to achieve this result, while in patients with a final eTICI score of 2B this decline had already occurred if more than two passes were necessary 6. Prolonged procedure time, greater infarct volumes, increased clot fragmentation with distal embolization, and accumulated endothelial damage after multiple passes are possible explanations for this negative effect of an increasing number of passes on functional outcome 13–16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation